2016
DOI: 10.1016/j.neuroimage.2015.09.073
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism at the core of the brain. Structural differences between bilinguals and monolinguals revealed by subcortical shape analysis

Abstract: Naturally acquiring a language shapes the human brain through a long-lasting learning and practice process. This is supported by previous studies showing that managing more than one language from early childhood has an impact on brain structure and function.However, to what extent bilingual individuals present neuroanatomical peculiarities at the subcortical level with respect to monolinguals is yet not well understood, despite the key role of subcortical gray matter for a number of language functions, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
87
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 100 publications
(114 reference statements)
13
87
4
Order By: Relevance
“…Following that, subcortical structures were segmented with FIRST (Patenaude et al 2011), an analysis tool implemented in FSL. Based on the effects reported in Burgaleta et al (2016), we automatically segmented the thalamus, globus pallidus, putamen, and the caudate nucleus. Quality control of the segmented images was performed by an experienced researcher.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following that, subcortical structures were segmented with FIRST (Patenaude et al 2011), an analysis tool implemented in FSL. Based on the effects reported in Burgaleta et al (2016), we automatically segmented the thalamus, globus pallidus, putamen, and the caudate nucleus. Quality control of the segmented images was performed by an experienced researcher.…”
Section: Methodsmentioning
confidence: 99%
“…Burgaleta et al (2016) suggested that this is because of the preferred method of use in the majority of these studies, i.e., VBM, which may not be optimal in accounting for the shape and size of subcortical structures (Zatorre et al 2012). To overcome this, Burgaleta and colleagues used the shape analysis technique FIRST (Patenaude et al 2011) which can account better for regional variations in the shape of subcortical structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in individuals who speak 3 languages or more, would be systematically and positively related to the volumes of these two subcortical structures. It is worth noting that two previous studies (Burgaleta et al, 2016;Pliatsikas, DeLuca, Moschopoulou, & Saddy, 2016) have found that the caudate nuclei of bilinguals are relatively larger compared to those of monolinguals.…”
Section: Introductionmentioning
confidence: 86%
“…The caudate nuclei have been shown to play a role in both language control (Crinion et al, 2006;Hervais-Adelman et al, 2015) and cognitive control (Grahn, Parkinson, & Owen, 2008), and have previously been shown to be enlarged in bilinguals vs. monolinguals (Burgaleta et al, 2016;Pliatsikas, DeLuca, Moschopoulou, & Saddy, 2016). Although there is also evidence for a role of the putamen in multilingual control, it may be that the absence of an observed relationship between putaminal structure and LEXP is due to the nature of its role: if, as suggested by Hervais-Adelman and colleagues (2015), the caudate is implicated in managing lexico-semantic sets as a function of task demands (c.f.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%